Modulation of the immune response to pneumococcal type 14 capsular polysaccharide-protein conjugates by the adjuvant Quil A depends on the properties of the conjugates. - Verheul, A F (1989)
Streptococcus pneumoniae type 14 capsular polysaccharide-bovine serum albumin (S14PS-BSA) conjugates were prepared by water-soluble-carbodiimide-mediated condensation with or without the use of N-hydroxy-sulfosuccinimide. The immunogenicities of the capsular polysaccharide (S14PS) and of the conjugates were studied in (CBA/N x BALB/c)F1 mice and in female BALB/c mice. The response in these mice indicates that S14PS could be classified as a thymus-independent type 2 antigen. Coupling of S14PS to BSA improved the immunogenicity of this polysaccharide, and an immunoglobulin G memory response was evoked. Conjugation with N-hydroxysulfosuccinimide resulted in a product with a higher polysaccharide/protein ratio. This conjugate induced a greater immune response than did the classical conjugate. Quil A enhanced the immune response to S14PS and to most S14PS-BSA conjugates. The enhancement of the immune response to the conjugates seemed to depend on the coupling procedure. Our results indicate that for the construction of immunostimulating complexes based on polysaccharide or oligosaccharide-protein conjugates, attention should be paid to the degree of cross-linking of the antigens involved.